Arterial and Venous Thrombosis in Patients with Myeloproliferative Neoplasms - Sukrisman, Lugyanti (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Myeloproliferative neoplasm (MPN) is a hematologic disorder that consists of polycythemia vera (PV), essential thrombocythemia (ET and primary myelofibrosis (PMF) and complication of thrombosis is frequently found in patients with MPN. This study was conducted to observe complication of thrombosis in patients with MPN. Methods. A descriptive study was conducted among patients with MPN at MMC Hospital. Clinical data was obtained from medical records of patients with MPN who sought treatment with investigator between 2010 and 2018 and the data was collected consecutively. Evaluation on JAK2 mutation was performed at either the Research and Development Laboratory of Dharmais Cancer Hospital or Kalgen® Laboratory. Complication of thrombosis was found based on radiological data, which could provide evidences on the presence of thrombosis except for complication of sudden deafness and erythromelalgia, which were found based on clinical diagnosis. Results. We found 23 subjects with MPN during the study period, which consisted of 12 subjects with PV, 8 subjects with ET, 2 subjects with PMF and 1 subject with post-ET MF. Evaluation on JAK2 mutation was performed in 16 out of 23 subjects. Thirteen subjects showed mutation of JAK2 gene except in 2 subjects with PMF and 1 subject with ET, who did not show V617F mutation of JAK2 gene. Subject with JAK2 mutation aged between 45 – 71 years. Complications were found in 12 out of 23 MPN subjects including ischemic stroke, DVT, portal vein thrombosis, thrombosis of mesenteric veins and arteries, non-ST elevated myocardial infarction (NSTEMI), peripheral artery disease (PAD), sudden deafness and erythromelalgia. The thrombotic complications occurred in subjects with polycythemia vera, essential thrombocythemia and myelofibrosis, either primary or the post-ET. Ischemic stroke is the most common complication, i.e. in 6 out of 12 (50%) of those with thrombotic complication and in all of subjects with polycythemia vera. There were 2 subjects experienced 2 multiple thromboses at unusual sites with consecutive episodes despites anticoagulant therapy, i.e. thrombosis of portal vein followed by mesenteric artery; and thrombosis of portal vein and mesenteric vein simultaneously followed by non-ST elevated myocardial infarction (NSTEMI) in less than 2 months. Both subjects experienced multiple thromboses during full-dose of anticoagulant therapy. Conclusions. Complication of thrombosis in MPN patients may exist in the form of arterial and venous thrombosis with ischemic stroke as the most common complication in subjects with polycythemia vera. Multiple thrombosis and splanchnic thrombosis as portal vein, mesenteric vein and artery thrombosis can also be found in subjects with MPN.